Efficacy of brentuximab vedotin in patients with CD30-positive lymphoproliferative skin diseases: results of the first prospective study in the Russian Federation - Irena E. Belousova; Liliya G. Gorenkova; Sergei K. Kravchenko; Alla M. Kovrigina; Elena E. Lepik; Tatiana V. Shneyder (State Scientific Center of Dermatovenereology and Cosmetology, 2022)
Background. Primary cutaneous lymphomas are the second most common group of extranodal lymphomas. Unlike nodal lymphomas, where B-cell proliferations dominate, primary cutaneous T-cell lymphomas account for 6575% of all cutaneous lymphomas. Among T-cell lymphomas of the skin, about 50% of cases are mycosis fungoides (MF), the second place in frequency of occurrence is occupied by CD30-positive lymphoproliferative skin diseases (CD30 LPD), about 10% are rare nosological forms, such as primary cutaneous peripheral T-cell lymphoma, unspecified, Sezari syndrome (SS), etc. During the initiating treatment of patients with MF and Szary syndrome (SS), carried out on the territory of the Russian Federation, for about 30% of patients are resistant to various therapeutic effects, especially in the later stages. The problem of the treatment of CD30+ LPD is extracutaneous dissemination in case of primary cutaneous anaplastic large cell lymphoma (pcALCL), steadily relapsing course of lymphomatoid papulosis (LyP) without symptom-free intervals. These characteristics of the therapy of cutaneous lymphomas demand for the need to search for new treatment options. Brentuximab vedotin, according to the results of the international randomized ALCANZA trial, has shown high efficiency in the treatment of cutaneous T-cell lymphoproliferative diseases. Aim. To evaluate the efficacy of brentuximab vedotin application in patients with cutaneous T-cell lymphomas in adverse risk group received at least one line of systemic therapy. Materials and methods. The study included 21 patients: 16 men and 5 women. The diagnosis of MF was verified in 8 patients, SS in 5 patients, cutaneous CD30+ LPD in 6 patients (5 patients pcALCL, 1 patient LyP) and a primary cutaneous peripheral T-cell lymphoma, unspecified in 2 patients. The diagnosis of cutaneous T-cell lymphoma was verified on the basis of the anamnesis of the disease, on the character of cutaneous lesions, on histological, immunohistochemical and in some cases on molecular genetic testing of the skin biopsy (the assessment of T-cell receptor gene rearrangement). Results. The late stages of the disease were diagnosed in 12 of 13 patients with MF/SS. Extracutaneous lesions were diagnosed in 57% of cases. The median of prior lines therapy was 3 (18 variants of treatment). The overall response to the treatment was achieved in 91% of cases (in 19 of 21 patients): the complete remission was obtained in 53% of cases, very good partial remission in 31% of cases and partial remission in 16% of cases. The progression of the disease was determined in 2 patients (after the first and fourth cycles). Some patients with partial remission as a result of therapy using brentuximab vedotin had the additional therapy (radiation therapy, interferon , the cycles of systemic therapy) and these acts gave an option of achieving deeper antitumor response. The early relapse was diagnosed in 2 of 19 patients who had responded to the treatment. The treatment tolerability was acceptable, and the toxicity did not exceed the already known one described in earlier studies. Thus, the stable overall antitumor response had been persisting in 89% of patients (the median of the observation was 10 months). Conclusion. The use of targeted therapy with brentuximab vedotin gave an option of achieving high treatment results in group of patients with advanced stages of the disease and inefficiency of several lines of therapy.